The complete chloroplast genomes of Camellia chrysanthoides and Camellia achrysantha - Yanchi Lai; Shaoqing Tang (Mitochondrial DNA. Part B. Resources, 2021)
Camellia chrysanthoides H. T. Chang and Camellia achrysantha H. T. Chang et S. Y. Liang are two threatened yellow camellia species endemic to southwestern Guangxi, China. Here, we report the complete chloroplast (cp) genomes of C. chrysanthoides and C. achrysantha for the first time. The total cp genome of C. chrysanthoides is 156,959 bp and contains a large single-copy (LSC, 86,564 bp) region, a small single-copy (SSC, 18,267 bp) region, and a pair of inverted repeat (IR, 26,064 bp) regions. The cp genome of C. achrysantha is 156,658 bp and includes an LSC region of 86,249 bp, SSC region of 18,243 bp, and two IR regions of 26,083 bp each. Both C. chrysanthoides and C. achrysantha have 136 genes, including 93 protein-coding genes, 35 tRNA genes, and eight rRNA genes.